Evaluation of analgesic activity of perindopril in albino mice - R N Suresha; Siddamma Amoghimath; P S Vaibhavi; S L Shruthi; M K Jayanthi; H L Kalabharathi (Wolters Kluwer Medknow Publications, 2014)
The aim was to evaluate the analgesic activity of perindopril in chemical, thermal and mechanical pain on Swiss albino mice. A total of 54 albino mice (Swiss strain) weighing 25-30 g were allocated to each experimental model and in each model there were three groups. The control group received normal saline (25 ml/kg) per orally, standard group received pentazocine (10 mg/kg) intra-peritoneal and test groups received perindopril (1 mg/kg) per orally. Perindopril and normal saline was administered 2 h before, whereas the pentazocine was administered 15 min prior to Eddy's hot plate, writhing and tail clip methods. The decrease in number of writhes, the delay in reaction time in tail clip and Eddy's hot plate method denoted the analgesic activity. Perindopril decreased the number of writhes, delayed the reaction time in tail clip and Eddy's hot plate method considerably when compared with control (normal saline), but less when compared with standard (pentazocine). Perindopril exhibits analgesic activity in thermal, chemical, and mechanical pain models in albino mice.